PERTIMBANGAN HAKIM DALAM PENETAPANPERKAWINAN BEDA AGAMA(Analisis Putusan No. 109/Pdt.P/2014/PN.SKA) - RARASATI, ERMA DEWI; , Mutimatun Ni'ami ,SH. M.Hum; , Aristya Windiana P. SH.MH (2015)
Erma Dewi Rarasati. NIM. C. 100100017. Consideration Judge In Different Religious Marriage Determination (Analysis of Decision No. 109 / Pdt.P / 2014 / PN.SKA). Faculty of Law. Muhammadiyah University of Surakarta. 2015. The purpose of this study was to analyze the consideration of judges in imposing the determination of the interfaith marriage license application in Surakarta District Court judges as well as to analyze consideration in the determination of the interfaith marriage license application in terms of Act No. 1 of 1974 on Marriage. This research is a normative juridical research, the study examines how law that promotes library materials or materials called secondary data, in the form of positive law and how its implementation in practice. Source data using secondary data from Surakarta District Court. Data were analyzed using qualitative analysis. The results showed that: (1) Consideration of Justice in Making a Marriage License Application Determination Against Religious Differences in Surakarta District Court is a) Social aspects: marriage is the behavior of the One God's creatures in the life of the natural world in order to breed, based on humanity; b) Juridical Aspects: The jurisprudence of the Supreme Court of the Republic of Indonesia dated January 20, 1989 registers Number 1400K / Pdt / 1986, explaining that religious differences for the prospective husband and wife are not forbidden for them to carry out the marriage; (2) Consideration of Judges in the Marriage License Application Determination Against Religious Differences Seen from Law No. 1 of 1974 on Marriage is because Act No. 1 of 1974 on Marriage in particular Article 66 which states: "For the marriage and everything related to the marriage based on this Act, then by the enactment of this Act the provisions set out in the Code of Civil Law (burgelijk Wetboek), Indonesia Christian Marriage Ordinance (Huwelijk Ordanantie Indonesia Christen 74 1933, Mixed Marriage Regulations ( Regeling op gemeng de Huwelijken S.1898 No. 158), and other regulations governing marriage so far been regulated in this Law, declared null and void ". Keywords: interfaith marriage, marriage law